Development and Use of an Endpoint Titration Assay To Characterize Mumps IgG Avidity following Measles, Mumps, and Rubella Vaccination and Wild-Type Mumps Infection - Sara Mercader (American Society for Microbiology, 2018)
ABSTRACT Waning mumps IgG antibody and incomplete IgG avidity maturation may increase susceptibility to mumps virus infection in some vaccinees. To measure mumps IgG avidity, serum specimens serially diluted to the endpoint were incubated on a commercial mumps-specific IgG enzyme immunoassay and treated with the protein denaturant diethylamine (60 mM, pH 10). End titer avidity indices (etAIs [percent ratio of detected diethylamine-resistant IgG at endpoint]) were calculated. Unpaired serum specimens (n = 108) from 15-month-old children living in a low-incidence setting were collected 1 month and 2 years after the first measles, mumps, and rubella vaccine dose (MMR1) and tested for mumps avidity. Per the receiver operating characteristic curve, the avidity assay is accurate (area under the curve, 0.994; 95% confidence interval [CI], 0.956 to 1.000), 96.5% sensitive (95% CI, 87.9 to 99.6%), and 92.2% specific (95% CI, 81.1 to 97.8%) at an etAI of 30%. When 9 sets of paired serum specimens collected 1 to 60 months post-MMR1 were tested for mumps and measles IgG avidity using comparable methods, the mumps etAI increased from 11% to 40 to 60% in 6 months. From 6 to 60 months, avidity was sustained at a mean etAI of 50% (95% CI, 46 to 54%), significantly lower (P  < 0.0001) than the mean measles etAI of 80% (95% CI, 74 to 86%). Mean etAIs in children 2 years post-MMR1 (n = 51), unvaccinated adults with distant mumps disease (n = 29), and confirmed mumps cases (n = 23) were 54, 62, and 57%, respectively. A mumps-specific endpoint avidity assay was developed and validated, and mumps avidity was determined to be generally sustained at etAIs of 40 to 60%, reaching etAIs of >80% in some individuals. IMPORTANCE Numerous outbreaks of mumps have occurred in the United States among two-dose measles-mumps-rubella (MMR)-vaccinated populations since 2006. The avidity of mumps-specific IgG antibodies may affect susceptibility to mumps virus infection in some vaccinated individuals. To accurately measure mumps avidity, we developed and validated a mumps-specific IgG avidity assay that determines avidity at the endpoint titer of serially diluted serum specimens, providing results that are independent of IgG concentration. At low antibody titers, endpoint methods are considered more accurate than methods that determine avidity at a single dilution. We determined that 6 months after the first MMR dose, mumps IgG avidity is high and generally sustained at avidity indices of 40 to 60%, reaching values of >80% in some individuals. Additionally, 4% (4/103) of individuals had avidity indices of ≤30% (low avidity) 2 years after vaccination. Inadequate mumps avidity maturation may be one factor influencing susceptibility to mumps virus infection among previously vaccinated or naturally infected individuals.